Relatório Independente da Iniciativa de Transparência na Indústria Extractiva - EITI (Extractive Industries Transparency Initiative (EITI), 2020)
Este é o nono relatório de reconciliação dos pagamentos efectuados pelas empresas que operam na indústria extractiva e os recebimentos do Estado. Foram reconciliadas 97% das receitas tributárias provenientes da indústria extractiva. As diferenças apuradas entre os pagamentos das empresas e os recebimentos do Estado correspondem a 0,17% dos montantes confirmados pelo Estado em 2019.
Keywords: *tagged; FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; extractive industries / indústrias extractivas; natural resources / recursos naturais

Como Está Cabo Delgado? Webinar 2: Economia Política Dos Recursos Naturais - Observatório do Meio Rural (2020)
Com a entrada no novo milénio, e em virtude do aumento da procura de matérias primas nos mercados internacionais, intensifica-se um modelo de desenvolvimento assente na exploração de recursos naturais. Em Cabo Delgado emerge uma economia extractiva, fortemente dirigida para mercados externos e dependente da oscilação de preços nos mercados internacionais, que o país não tem condições de controlar. Grandes multinacionais envolvem-se numa acesa competição pelo acesso a recursos, em complexas alianças com elites nacionais, também elas em disputa entre si. Neste webinar pretende-se reflectir sobre as lógicas de acumulação aqui envolvidas, assim como o impacto que poderá ter para Moçambique em termos de receitas fiscais, e de desenvolvimento nacional.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - portuguese / português; M - political economy analysis (PEA) / análise de economia política (AEP); extractive industries / indústrias extractivas; natural resources / recursos naturais

Inclusive Land Governance in Mozambique: Good Law, Bad Politics? - Cabral, Lídia; Norfolk, Simon (IDS Working Papers, 2016)
This paper analyses inclusive land governance in Mozambique. It focuses on the country’s legal framework and the DUAT, the right to use and benefit from the land. The DUAT is a distinctive element of the Mozambican legislation that has land as the property of the state but recognises land use rights for occupants and users on the basis of a unitary system of tenure. The challenges of putting in practice what is thought to be one of Africa’s most progressive legal frameworks are discussed. These are set against a context where despite land abundance there are concerns over land grabbing and dispossession of rural communities, which constitute over 70 per cent of the country’s population. The law may be progressive but government politics are not, as an increasingly hegemonic elite controls Mozambique’s political system and resources. In the Mozambican context, we addressed these themes and questions at two levels: the national level that concerns legal frameworks, institutional players, policies and processes, complemented by a focus on land governance practices at the local level. We selected the province of Nampula, in Northern Mozambique, as the focus of our analysis of local practices. The main reason for this choice was the strategic location of the province within the Nacala corridor, an area extending along the transport corridor connecting the Mozambican hinterland to the seaport at Nacala. The Nacala corridor is a region of rapid economic expansion that has been stimulated by the development of the transport network that comprises the railway connecting Nacala to the coal mine explored by Vale in Tete province, one of the largest foreign investments in Mozambique. Unsurprisingly, there has been considerable pressure over land for agriculture, forestry, mining as well as transport infrastructures and the corridor has become a hot spot for some of the most high-profile cases of land conflict in Mozambique (UNAC and GRAIN 2015). Nampula is also one of SDC’s target provinces.
Keywords: *indexed; *tagged; DUAT (Direito do uso e aproveitamento da terra) / Land Use and Benefit Right; G - Mozambique / Moçambique; G - Nacala; G - north / norte; GP - Nampula; L - english / inglês; M - political economy analysis (PEA) / análise de economia política (AEP); Northern PEA; agriculture / agricultura; extractive industries / indústrias extractivas; governance / governação; land governance / gestão de terra; law / direito; ⛔ No DOI found

Overblown expectations of the mining sector - Economist Intelligence (Economist Intelligence, 2016)
The government of Mozambique remains confident that its mining boom is set to accelerate in the coming years, despite weak sentiment in the global mining industry. Rising coal production and an eventual rebound in global prices will spur some growth in Mozambique's mining sector in 2016‑20 but we expect that, weighed down by infrastructure deficits and non-competitive policies, it will remain a relatively small contributor to GDP growth. Mozambique has untapped coal reserves estimated to be in excess of 20bn tonnes, as well as commercial quantities of aluminium, gold, titanium, graphite and gemstones. Plus, it benefits from a long coastline and geographic proximity to mineral-hungry markets in Asia. At the peak of the commodity super-cycle, investor interest in Mozambican mining soared; the contribution of the mining sector to GDP increased from 1.6% in 2009 to 3.2% in 2013, while government earnings from the sector swelled from US$40m in 2009 to over US$1bn in 2014.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; extractive industries / indústrias extractivas; natural resources - mining / recursos naturais - mineração; natural resources / recursos naturais